Divine Animals - Mariño Ferro, Xosé Ramón (2020)
This article is about divine animals in Egypt; of the comments they deserved from renowned Greco-Latin authors; of the reasons for its use. It also deals with some divine animals in Christianity and the survival of certain Egyptian iconographic motifs in the Middle Ages.   Bibliography Printed sources AGUSTÍN DE HIPONA – Cartas. Madrid: BAC, 1952. AMBROSIO DE MILÁN – La virginidad. Madrid: Ciudad Nueva, 2007. APULEYO – El asno de oro. Madrid: Gredos, 2001. ARISTÓTELES – Historia de los animales. Madrid: Akal, 1990.  BEATO DE LIÉBANA – Comentario del Apocalipsis. Madrid: 1995.   BERCEO – Milagros de Nuestra Señora. Madrid: Castalia, 1980. BLÁZQUEZ, José Mª; LARA, Federico (Eds.) – El libro de los muertos. Madrid: Editora Nacional, 1984.  ELIANO – Historia de los animales. Madrid: Gredos, 1984, 2 vols. FILÓSTRATO – Vida de Apolonio de Tiana. Madrid: Gredos, 2002. HERÓDOTO – Historia. Madrid: Gredos, 2001, 5 vols. HOMERO – Ilíada. Madrid: Gredos, 2006. HORAPOLO – Hieroglyphica. Madrid: Akal, 1991. ISIDORO DE SEVILLA – Etimologías. Madrid: BAC, 1982. JUVENAL – Sátiras. Madrid: Gredos, 2001. LONGO – Dafnis y Cloe. Madrid: Gredos, 1982. LUCIANO DE SAMOSATA – Obras. Madrid: Gredos, 2002, 4 vols. MÁXIMO DE TIRO – Disertaciones filosóficas. Madrid: Gredos, 2005. MONTAIGNE, Michel de – Ensayos completos. Madrid: Cátedra, 2008. PÍNDARO – Obra completa. Madrid: Cátedra, 1988. PLUTARCO – Obras morales y de costumbres (Moralia). Madrid: Gredos, 1987, 10 vols. PORFIRIO – Sobre la abstinência. Madrid: Gredos, 1984. VORÁGINE, Santiago – La leyenda dorada. Madrid: Alianza, 1982.   Studies FRANKFORT, Henri – Reyes y dioses. Madrid: Alianza, 1988. GERMOND, Philippe, LIVET, Jacques – An Egyptian bestiary: animals in life and religion in the land of the Pharaohs. London: Thames and Hudson, 2001. GONZÁLEZ HERMOSO, Irene – “El Tetramorfo”. Revista Digital de Iconografía Medieval [Em línea] III/5 (2011), p. 61-73. [Consultado en 2 Octubre 2019]. Disponible en https://www.ucm.es/data/cont/docs/621-2013-11-21-8.%20Tetramorfo.pdf. GOODMAN, Steven M., MEININGER, Peter L. –  The birds of Egypt. Oxford: Oxford University Press, 1989. HORNUNG, Erik – El Uno y los Múltiples. Madrid: Trotta, 2016.  HOULIHAN, Patrick F. – The birds of Ancient Egypt. Warminster: Aris & Phillips, 1986. LÓPEZ GRANDE, María José – Damas aladas del Antiguo Egipto. Barcelona: Museu Egipci, 2003. MÂLE, Emile – El arte religioso del siglo XIII en Francia. Madrid: Encuentro, 2001. MARIÑO FERRO, Xosé Ramón – Diccionario del simbolismo animal. Madrid: Encuentro, 2014. MARIÑO FERRO, Xosé Ramón – Suma de mitología clásica. Saarbrüken: Editorial Académica Española, 2017, 3 vols. MEEKS, Dimitri – “Zoomorphie et image des dieux dans l’Égypte ancienne”. in MALAMOUD, Charles ; VERNANT, Jean-Pierre – Corps des dieux. Le temps de la réflexion VII. Paris: Éditions Gallimard, 1986. RÉAU, Louis – Iconografía del arte cristiano. Iconografía de la Biblia. Nuevo Testamento. Barcelona: Ediciones del Serbal, 2008. REDFORD, Donald B. (Ed.) – Hablan los dioses. Barcelona: Crítica, 2003. RIPA, Cesare – Iconología. Madrid: Akal, 1987, 2 vols. SALES, José das Candeias – “A metalinguagem religiosa: as aves como metáforas e símbolos na mitologia egípcia”. Revista Lusófona de Ciência das Religiões 20 (2017), pp. 7-41. SÉBILLOT, Paul – La faune. Paris: Imago, 1984. VERNUS, Pascal; YOYOTTE, Jean – Bestiaire des pharaons. Paris: Éd. Perrin, 2005. WILKINSON, Richard H. –  Cómo leer el arte egipcio. Barcelona: Crítica, 1998. WILKINSON, Richard H. – Magia y símbolo en el arte egipcio. Madrid: Alianza, 2003. WILKINSON, Richard H. – Todos los dioses del Antiguo Egipto. Madrid: Oberón, 2003.